Therapeutic singing-induced swallowing exercise for dysphagia in advanced-stage Parkinson’s disease - Yeo, Myung Sun; Hwang, Jihye; Lee, Hye Kyoung; Kim, Soo Ji; Cho, Sung-Rae (Frontiers in Neurology, 2024)
Background With longer life spans and medical advancements, the rising number of patients with advanced-stage Parkinson’s disease (PD) warrants attention. Current literature predominantly addresses dementia and fall management in these patients. However, exploring the impact of swallowing function on patients with advanced PD is crucial. Previous research has demonstrated notable enhancements in the quality of life related to voice for participants following a group singing-intervention program. To further elucidate the effect of individual singing-induced swallowing exercises, our study aimed to investigate the quantitative and qualitative effects of therapeutic singing on swallowing function in patients with advanced PD in comparison to a matched usual care control group. The hypothesis of this study is that therapeutic singing-induced swallowing exercises can assist to maintain swallowing function in patients with advanced PD. Methods This prospective matched control study compared the effects of a 6-week therapeutic singing-based swallowing intervention on swallowing function and quality of life in patients with advanced PD. The intervention group received individual sessions with a music therapist and conventional individual physical therapy. The control group received the same standard physical therapy for 6 weeks without music intervention. The primary outcome measure was Video Fluoroscopic Dysphagia Scale (VDS). Results The study revealed that the intervention group maintained swallowing function, whereas the control group experienced deterioration, indicating significant time-dependent changes in Penetration-Aspiration Scale (PAS), National Institutes of Health-Swallowing Safety Scale (NIH-SSS), and VDS. Analysis of PAS and NIH-SSS liquid food scores in both groups showed significant time effects. However, the intervention group exhibited no significant differences between the pre- and post-tests, indicating preservation of the swallowing function. VDS of liquid food indicated an interaction effect between time and group in the pharyngeal phase and total scores. The Swallowing-Quality of Life showed significant time-effect improvement in the intervention group. Conclusion Therapeutic singing exercises may help maintain swallowing function in advanced PD patients, potentially enhancing quality of life related to swallowing in those with advanced-stage diseases. Clinical trial registration https://cris.nih.go.kr/cris/search/listDetail.do, identifier KCT0008644.